Development of mobile based flood victims medical management system - Mohd Zabidi, Muhammad Izzat Zakwan; Musa, Amirul Ikmal; Abd Rashid, Wan Norhisyam; Harum, Norharyati; Rahmalan, Hidayah; Roslan, Irda; Khalid, Ahmad Khudzairi (Seventh Sense Research Group (SSRG), 2022)
Flood is the most devastating natural disaster Malaysia has ever seen. In Malaysia, including Sabah and Sarawak, there are 189 river basins (89 in Peninsula Malaysia, 78 in Sabah, and 22 in Sarawak), with the main rivers flowing directly into the South China Sea and 85 of them are prone to repeated floods. The projected area vulnerable to flood catastrophe is around 29,800 km2 or 9% of Malaysia's total territory, affecting nearly 4.82 million people or about 22% of the country's entire population. Humans are affected by floods in a variety of ways. Floods have the worst effect on human health because infectious illnesses spread readily during and after the flood. Furthermore, healthcare services are hampered during the flood season. It is owing to transportation and staffing difficulties, as well as the procedure of documenting flood victims' health reports. The primary goal of this initiative is to assist flood victims in terms of health. It will be easier to seek treatment, record the patient's health concerns online, and notify the hospital immediately if there are patients who need to be sent to the hospital with the information supplied. This system was created with the Android Studio platform as the user interface medium and Google Firebase as the data storage medium.